Inclusion of Participants with CKD and Other Kidney-Related Considerations during Clinical Drug Development: Landscape Analysis of Anticancer Agents Approved from 2015 to 2019. Issue 4 (6th April 2023) - Butrovich, Morgan A.; Reaves, Allison C.; Heyward, Jamie; Moore, Thomas J.; Alexander, G. Caleb; Inker, Lesley A.; Nolin, Thomas D.
Visual Abstract: Abstract : Background: The US Food and Drug Administration has prioritized efforts to expand availability of therapies, including anticancer agents, for patients with CKD. US Food and Drug Administration Guidance recommends inclusion of study participants with CKD in clinical trials, improving pharmacokinetic characterization in people with decreased GFR, and using contemporary GFR assessment methods during drug development. We performed a landscape analysis of anticancer agents approved from 2015 to 2019 to evaluate inclusion of study participants with CKD and GFR assessment methods used during drug development and subsequent translation to kidney-related safety and dosing data in product labeling. Methods: Oncology drugs approved from 2015 to 2019 and associated pivotal trials were identified. We evaluated inclusion of study participants with CKD in pivotal trials and pharmacokinetic analyses, investigated GFR assessment methods used for pivotal trial eligibility and renal pharmacokinetic analyses, and identified kidney-related adverse drug event and dosing information. Results: A total of 55 drugs and 74 pivotal trials were included. Of the pivotal trials, 95% contained kidney-related eligibility criteria, including 68% with GFR-based eligibility. The median lower limit of GFR required for inclusion was 45 ml/min or ml/min per 1.73 m 2 . Pharmacokinetic analyses were performed in CKD stages 4–5 and hemodialysis for only 29% and 6% of drugs, respectively. Estimated creatinine clearance was used in over 60% and 80% of pivotal trials and pharmacokinetic analyses, respectively. Reporting of kidney-related adverse drug events was highly variable. Product labeling for 49% of drugs contained no kidney dosing information. Conclusions: Study participants with CKD continue to be excluded from anticancer drug development, and GFR estimation in pivotal trials and renal pharmacokinetic analyses remains imprecise and heterogeneous. Furthermore, kidney-related safety and dosing information is scarcely and inconsistently presented.